Simplying the management of patients with bipolar disorder and/or schizophrenia with extended-release quetiapine as adjunct treatment. Issue 2 (12th March 2012) - Pérez, J.C.; Mas, P.; Nigorra, M.; Vilanova, M.; Bravo, C.; Calderon, B.; Crespo, J.M.
Abstract : Background: Lack of adherence leads to frequent emergency visits and an increased number of hospital readmissions. Several studies have shown that once a day dosing (simplification of treatment (ST)) may improve adherence. Purpose: To assess ST at discharge, with initiation of, or change to, extended release quetiapine (QXR) in patients admitted to a psychiatric unit diagnosed with bipolar disorder (BD) and/or schizophrenia (SCH). Materials and methods: Retrospective study (February 2010-April 2011) of QXR prescription in BD and/or SCH from the admission and discharge reports. ST: reduction of one or more drugs and/or two or more tablets/times a day. Each administration of drops was equivalent to one tablet. Data were measured at admission and discharge: ▶ number and types of drugs, doses and tablets. ▶ QXR dosage at discharge. Results: 18 patients (8 men) aged 25-67 years (mean 44 ±12 years) in 19 admissions (16 BD, 3 SCH). 4 were excluded, all with BD, because QXR was discontinued. Type of drug at discharge: Antipsychotics: 93% had an antipsychotic other than QXR (mainly clozapine), 80% had more than 2 and 40% over 3. 20% reduced the number of antipsychotics. Benzodiazepines: 47% increased the number of different benzodiazepines and 13% got a decrease. Antidepressants: only 1 patient had antidepressants, related to a reduction of antipsychotics. Mood stabilisers: 33% had at least one at admission, and 60% more than one. Other: 60% were taking more 'other medicines' at discharge, 78% due to starting lithium. The treatment was simplified in 20% of patients: 1 patient reduced the number of drugs and tablets, 1 the number of doses and 1 the number of drugs. Conclusion: The proportion of patients with ST was very low in our series.